Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d3ta03249c
|View full text |Cite
|
Sign up to set email alerts
|

Towards low-temperature processing of efficient γ-CsPbI3 perovskite solar cells

Abstract: Inorganic cesium lead iodide (CsPbI3) perovskite solar cells (PSCs) have attracted enormous attention due to their excellent thermal stability and optical bandgap (~1.73 eV), well-suited for tandem device applications. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Recently, benefiting from the merits of high hole selectivity, efficient hole transfer, and low interface trap density, the carbazole core-based phosphonic acid self-assembled monolayers (SAMs) have been proven to be a promising HTL and enabled significant performance enhancements in both single-junction and perovskite-based tandem solar cells. With covalent binding to the substrate surface, these SAMs are relatively tolerant against perovskite processing and could potentially offer a nanoscale conformal coverage on textured surfaces. Moreover, SAMs not only regulate energy levels and surface wettability but also passivate interfacial trap states and provide low transport losses. Nevertheless, it is found that the related application of SAMs in inverted inorganic PSCs is still extremely limited compared with those in organic–inorganic hybrid perovskite systems, , where the recorded PCE has exceeded 25% . Thus, this spurred us to expand the application of SAMs to inorganic PSCs and explore whether SAMs can also promote the performance of inverted CsPbI 3 PSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, benefiting from the merits of high hole selectivity, efficient hole transfer, and low interface trap density, the carbazole core-based phosphonic acid self-assembled monolayers (SAMs) have been proven to be a promising HTL and enabled significant performance enhancements in both single-junction and perovskite-based tandem solar cells. With covalent binding to the substrate surface, these SAMs are relatively tolerant against perovskite processing and could potentially offer a nanoscale conformal coverage on textured surfaces. Moreover, SAMs not only regulate energy levels and surface wettability but also passivate interfacial trap states and provide low transport losses. Nevertheless, it is found that the related application of SAMs in inverted inorganic PSCs is still extremely limited compared with those in organic–inorganic hybrid perovskite systems, , where the recorded PCE has exceeded 25% . Thus, this spurred us to expand the application of SAMs to inorganic PSCs and explore whether SAMs can also promote the performance of inverted CsPbI 3 PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SAMs not only regulate energy levels and surface wettability but also passivate interfacial trap states and provide low transport losses. 32−35 Nevertheless, it is found that the related application of SAMs in inverted inorganic PSCs is still extremely limited compared with those in organic− inorganic hybrid perovskite systems, 36,37 where the recorded PCE has exceeded 25%. 38 Thus, this spurred us to expand the application of SAMs to inorganic PSCs and explore whether SAMs can also promote the performance of inverted CsPbI 3 PSCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 17 ] Therefore, the possibility to reduce the annealing temperature of CsPbI 3 and the implementation of such HTLs could be an alternative strategy to further improve the performance of all‐inorganic PSCs. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[17] Therefore, the possibility to reduce the annealing temperature of CsPbI 3 and the implementation of such HTLs could be an alternative strategy to further improve the performance of all-inorganic PSCs. [18] In this direction, many efforts have been made to reduce the annealing temperature of CsPbI 3 , such as the use of molten salts as perovskite solvents, [19,20] the application of vacuum treatment to the as-deposited perovskite layer, [21,22] increasing the annealing time, [23,24] adding sequential annealing steps at increasing temperatures, [25,26] or performing a preannealing step in nitrogen atmosphere followed by second annealing in humid air. [27] Despite the remarkable results achieved with these strategies, the additional levels of complexity induced in device processing partially drawback the potential of these approaches.…”
mentioning
confidence: 99%